2015
DOI: 10.5194/amt-8-4587-2015
|View full text |Cite
|
Sign up to set email alerts
|

EARLINET: potential operationality of a research network

Abstract: In the framework of ACTRIS (Aerosols, Clouds, and Trace Gases Research Infrastructure Network) summer 2012 measurement campaign (8 June–17 July 2012), EARLINET organized and performed a controlled exercise of feasibility to demonstrate its potential to perform operational, coordinated measurements and deliver products in near-real time. Eleven lidar stations participated in the exercise which\ud started on 9 July 2012 at 06:00 UT and ended 72 h later on 12 July at 06:00 UT. For the first time, the single calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…Next, Sicard et al (2015) report about an experiment around the Mediterranean basin in July 2012. Eleven EARLINET stations performed continuous measurements over a period of 72 h. This experiment is used as a demonstration for the capability of EARLINET to monitor special events and to deliver SCC products in real time or near realtime.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Sicard et al (2015) report about an experiment around the Mediterranean basin in July 2012. Eleven EARLINET stations performed continuous measurements over a period of 72 h. This experiment is used as a demonstration for the capability of EARLINET to monitor special events and to deliver SCC products in real time or near realtime.…”
Section: Validationmentioning
confidence: 99%
“…Unfortunately, the SCC was not yet finished at that time, and thus, the publication of scientifically quality assured EARLINET data of this event lasted 2 years (Pappalardo et al, 2013). Meanwhile, the SCC has become available and Sicard et al (2015) demonstrated its ability to deliver backscatter and extinction profiles in near real-time during an intense field campaign in the Mediterranean basin in summer 2012.…”
Section: Introductionmentioning
confidence: 99%
“…This conversion is often used to convert lidar-derived optical properties into mass concentration to test and evaluate transport models (Pérez et al, 2006;Sicard et al, 2015). Lately, POLIPHON is also used to extract the fractions of the high, moderate or low depolarizing particles from the total extinction, which can then be converted separately into mass concentration Ansmann, 2014, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The measurements started on 9 July at 06:00 UT and continued without interruption for 72 h whenever the atmospheric conditions allowed lidar measurements. The details of this quite intensive observation period are provided in Sicard et al (2015). The main aim of the 72 h operationally exercise was to provide a large set of aerosol parameters obtained in a standardized way for a large number of stations in near-real time.…”
Section: Example Of Near-real-time Applicabilitymentioning
confidence: 99%
“…Currently, it has been used by 20 different EARLINET stations which have submitted about 2600 raw data files covering a very large time period (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Moreover, more than 5000 SCC optical products (about 3600 aerosol backscatter profiles and 1400 aerosol extinction profiles) have been calculated and used for different purposes like analysis of instrument intercomparisons (Wandinger et al, 2015), air-quality model assimilation experiment (Wang et al, 2014;Sicard et al, 2015), and ongoing long-term comparisons with manually retrieved products (Voudouri et al, 2015). The large usage and the long-term plan for the centralized processing system make the SCC the standard tool for the automatic analysis of EARLINET lidar data.…”
Section: Scc Descriptionmentioning
confidence: 99%